The Effects of Cooperative Interactive Learning Strategies to Improve Undergraduates’ Speaking Skills - Swaran Singh, Charanjit Kaur; Masa Singh, Tarsame Singh; Eng Tek, Ong; Md Yunus, Melor (International Journal of Psychosocial Rehabilitation, 2019)
This research presents the findings of a study relating to the effect of cooperative interactive learning strategies to improve undergraduates’ speaking skills in one of the selected public universities in Malaysia. The study was also carried out to find out the students’ attitudes towards cooperative interactive learning strategies. Participants included one hundred and fifty-two undergraduates taking Diploma in English Program. A pre-posttest survey research design was employed for the data collection and also to find out whether there was a significant difference between the speaking scores for the four groups after exposing students to the cooperative interactive learning strategies. The data obtained from the pre and posttests was analyzed with paired sample t test. The findings revealed that there was a statistically significant increase in pretest scores to posttest scores. The findings from the survey showed that the students’ exhibit positive attitudes towards the cooperative interactive learning strategies employed to improve their speaking skills. The findings implicate that cooperative interactive learning strategies may be beneficial for educators to nurture undergraduates’ motivation and confidence for speaking.